Efektivitas E-LKPD dalam Liveworksheets berbasis Problem Based Learning pada Materi Hukum Dasar Kimia terhadap Kemampuan Pemecahan Masalah Peserta Didik Fase E - Illahi, Annisa Ridho; Parbuntari, Hesty (Lembaga Yasin AlSys, 2025)
Problem-solving ability is a crucial skill that must be developed to help students navigate increasingly complex challenges. This study aims to determine the effectiveness of using e-LKPD in Liveworksheets integrated with problem-based learning on the topic of basic chemical laws in enhancing students’ problem-solving skills. The research employed a nonequivalent control group design, with a population comprising all Grade X Phase E students at SMA Negeri 3 Padang Panjang (277 students) during the odd semester of the 2024/2025 academic year. A sample of 66 students was selected through purposive sampling, consisting of classes X.E.3 and X.E.4. Data were collected through a problem-solving ability test. The results showed an average N-Gain of 70%, categorized as moderately effective. A hypothesis test was conducted to assess significant improvement after treatment, with normality and homogeneity tests confirming that the data were normally distributed and homogeneous. A t-test at a 0.05 significance level yielded tₕᵢₜᵤₙg (1.8685) > tₜₐᵦₑₗ (1.69), indicating that H₀ is rejected and H₁ is accepted. The study concludes that the use of e-LKPD in Liveworksheets based on problem-based learning significantly improves students’ problem-solving abilities in the topic of basic chemical laws. The implication is that interactive digital media, when integrated with problem-based learning approaches, can serve as an effective strategy for chemistry instruction in the digital era.